Subjective well-being and life satisfaction : a social psychological perspective - Maddux, James E. (New York, NY : Routledge, 2025)
"This comprehensive and updated new edition offers scholarly summaries of theory and research on the social psychological influences on subjective well-being and life satisfaction. Among the topics covered are types of relationships (e.g., romantic relationships, friendships, online relationships) and types of interactions with others (e.g., forgiveness, gratitude, helping behavior). It also examines broader social issues such as culture, socioeconomic status, religion, and well-being in the workplace. The latest edition includes new chapters on economic inequality, psychedelic social psychology, singlehood, social worth, and identity. Subjective Well-Being and Life Satisfaction: A Social Psychological Perspective is a rich and focused resource for graduate students, upper-level undergraduate students, and researchers in positive psychology and social psychology. It should also be of interest to social neuroscientists, mental health researchers, clinical and counselling psychologists, and anyone interested in the science of well-being"--
Keywords: Well-being.; Happiness; Emotions; Interpersonal relations; PSYCHOLOGY / Social Psychology; PSYCHOLOGY / Mental Health; BODY, MIND & SPIRIT / Spiritualism